Study on fatigue properties of post-fire bimetallic steel bar with different cooling methods. (June 2022) - Hua, Jianmin; Wang, Fei; Xue, Xuanyi
Highlights: Effects of cooling method on the low-cycle fatigue properties of BSB specimens are revealed. Metallographic structures of BSB specimens subjected to different cooling methods and exposure temperatures are studied. Relationship between the number of cycles to failure and dissipated energy properties are discussed. Abstract: Bimetallic steel bars (BSBs) composed of cladding (stainless steel) and substrate (carbon steel, also called black steel) are produced to improve the durability of reinforced concrete (RC) structures. Fire has a lasting effect on reinforcing steel. To assess the service ability of RC structures experiencing fire incidents, fatigue performances of BSB subjected to different exposure temperatures and cooling methods were investigated experimentally. After the heating test, the stainless steel cladding was tightly connected to the carbon steel substrate. When subjected to cooling in air (CIA), the metallographic structures of the substrate in the test specimens after 800 and 900 °C consisted of ferrite and lamellar and granular pearlite. Additionally, martensite was formed because of the quenching process caused by cooling in water (CIW). For BSB specimens subjected to CIA, the effect of temperature on the hysteresis curve is relatively small. When temperature exceeds 700 °C, the cyclic curve of test specimens subjected to CIW becomes slender. Failure performances of BSB specimens with different cooling methods were discussed. A predictive model was suggested to quantify the low-cycle fatigue properties of BSB specimens. Variation trends of stress and strain coefficients were discussed to reveal low-cycle fatigue performances comprehensively.